MANAGEMENT OF STRENGTHENING CHARACTER EDUCATION ACTIVITIES FOR STUDENTS AT STATE ISLAMIC RELIGIOUS COLLEGE IN INDONESIA (STUDY ON PTKIN IN JAVA AND SUMATRA) - Neliwati Neliwati; Zaini Dahlan (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This study aims to explore the implementation of the management of character education strengthening activities for students at state Islamic religious universities (PTKIN) in Indonesia, which includes four research focuses, namely: planning, organizing, implementing and assessing. This type of research is qualitative with a phenomenological approach. The instruments used in the study were observation, interviews, documentation studies and Focus Group Discussion (FGD). The research locations are IAIN Padangsidimpuan, North Sumatra and IAIN Syekh Nurjati Cirebon, West Java. The analysis of the data used includes two steps, namely reviewing the data based on the research topic and observing repeated meanings as the main theme or pattern of research. The results of this study indicate that: First, the planning of character education strengthening activities is carried out before the character education strengthening program with various coordination activities with the leadership, study programs to lecturers in the form of deliberation to determine things that need to be done in strengthening character education. Second, the process of division of labor is carried out in accordance with the organizational structure in the establishment of character education strengthening institutions at Ma'had Al-Jami'ah, at the study program and faculty level. Third, the implementation of strengthening character education is carried out synergistically between Ma'had al-Jami'ah activities with lecture activities in the form of coordination between the managers of Ma'had Al-Jami'ah and all study programs in each faculty at the PTKIN studied. Fourth, the assessment in character education strengthening activities is carried out in stages and coordinated according to a predetermined time.